Bibliometric analysis of sports studies in the "Journal Sport Area" - Yulingga Nanda Hanief (Journal Sport Area, 2021)
This study aims appreciate the Journal Sport Area for the achievement of a nationally accredited rank the 2nd in 2020 by evaluating the publication patterns and scientific progress of the Journal Sport Area between 2016 and 2020 which includes the most productive authors, the most productive institutions, the most cited articles, the number of citations, and the level of author collaboration. This research is a qualitative descriptive study with a bibliometric analysis approach. Bibliometric analysis is used to evaluate publication patterns and scientific progress by adding data visualization with the help of the VOSViewer application from bibliographic data, co-authorship, and co-occurrence of keywords. The results of the analysis showed that the number of articles produced per year is concluded to be consistent with an average of 20.4. The most productive writer is Fadli Surahman from Karimun University with 4 articles. The most productive institution is Riau Islamic University with 38 articles. The number of citations was 196 throughout 2017-2021. The level of collaboration of the Journal Sport Area before being accredited occurred in two types, namely publications carried out individually from 2016-2017 and collaboratively starting from 2018-2020. This study concludes that the pattern of publication and scientific progress in the Journal Sport Area has changed from year to year, which is marked by changes in the level of collaboration and an increase in the number of citations as well as the emergence of topics that have opportunities (research gaps) for further research. This research is useful for understanding questions related to scientific products such as the number of publications, contributors, keywords, countries, and institutions that are often used in journal articles. Research trends in the Journal Sport Area are learning strategies in physical education. The originality value of this study presents exclusive bibliometric analysis data and identifies the main trends of publication in journals from the beginning of its establishment in 2016 to being accredited SINTA 2 in 2020.